2019
DOI: 10.1002/14651858.cd004317.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve adherence and continuation of shorter-term hormonal methods of contraception

Abstract: Editorial group: Cochrane Fertility Regulation Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 4, 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…A recent Cochrane review did not find significant differences amongst hormonal contraception, levonorgestrel releasing system (LNG-IUS), and copper intrauterine device (Cu-IUD), although the studies were small, and of low to moderate quality (35). Anticipatory discussion around anticipated menstrual side effects can reduce discontinuation of the shorter acting methods (36).…”
Section: Contraceptive Counsellingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review did not find significant differences amongst hormonal contraception, levonorgestrel releasing system (LNG-IUS), and copper intrauterine device (Cu-IUD), although the studies were small, and of low to moderate quality (35). Anticipatory discussion around anticipated menstrual side effects can reduce discontinuation of the shorter acting methods (36).…”
Section: Contraceptive Counsellingmentioning
confidence: 99%
“…Absolute and relative contraindications should be reviewed prior to initiation (4,17). Common side effects including unscheduled bleeding, nausea, and headaches, should be discussed with the adolescent prior to initiation, as this improves continuation (36). Adolescents and young women can be counselled that they can take the CHC with a 4-or 7-day HFI, and/or can take cyclically or in extended cycle (Skipping periods).…”
Section: Combined Hormonal Contraceptionmentioning
confidence: 99%
“…However, the quality of healthcare interactions varies by provider, leading to disparities in counseling and provision of services for family planning [9,11,12]. Poor provider interactions may result in decreased use of health services, and higher discontinuation and dissatisfaction with services [13][14][15]. Understanding the ways that women's interactions with health providers shape their family planning decision-making is important to maximizing the quality and use of family planning services for all women throughout the life course.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, few studies focused on the effect of family planning interventions on discontinuation and switching. We found three systematic reviews which concluded to a low level of evidence on the effect of the strategies to improve continuation of hormonal methods of contraception [14][15][16]. Halpern et al, in 2013, reported that only three trials showed some bene t of strategies to improve adherence and continuation.…”
Section: Introductionmentioning
confidence: 99%
“…For Mack et al, 2019, intensive counseling and reminders (with or without educational information) may be associated with the improved continuation of shorter-term hormonal contraceptive methods when compared with usual family planning care. However, this should be interpreted with caution due to the low certainty of the evidence [15]. Cavallaro et al, in 2013, conducted a systematic review of the strategies to improve adherence and acceptability of hormonal methods of contraception.…”
Section: Introductionmentioning
confidence: 99%